Recent trends in molecular aggregates: An exploration of biomedicine - Heo, Jeongyun; Murale, Dhiraj P.; Yoon, Hey Young; Arun, V.; Choi, Sangkee; Kim, Eunha; Lee, Jun Seok; Kim, Sehoon (Aggregate, 2022)
Molecular aggregates are receiving tremendous attention, demonstrating immense potential for biomedical applications in vitro and in vivo. For instance, the molecular aggregates of conventional fluorophores influence the electronic excitation states of the aggregates, causing characteristic photophysical property changes. A fundamental understanding of this classical relationship between molecular aggregate structures and photophysics has allowed for innovative biological applications. The chemical characteristics of drug molecules generally trigger the formation of colloidal aggregates, and this is considered detrimental to the drug discovery process. Furthermore, nano-sized supramolecular aggregates have been used in biomedical imaging and therapy owing to their optimal properties for in vivo utility, including enhanced cell permeability, passive tumor targeting, and convenient surface engineering. Herein, we provide an overview of the recent trends in molecular aggregates for biomedical applications. The changes in photophysical properties of conventional fluorophores and their biological applications are discussed, followed by the effects of conventional drug molecule-aggregates on drug discovery and therapeutics development. Recent trends in the investigation of biologically important analytes with aggregation-induced emission are discussed for conventional and unconventional fluorophores. Lastly, we discuss nano-sized supramolecular aggregates used in imaging and therapeutic purposes, with a focus on in vivo utilization.
Keywords: Aggregation-induced emissions; Biological applications; Biomedical applications; Drug molecules; In-vivo; Molecular aggregate; Nano sized; Photophysical properties; Recent trends; Supramolecular aggregates; aggregation-induced emission; molecular aggregate; nanomedicine